Patterns of lacrimal dysfunction in primary biliary cirrhosis. - Giovannini, A (1985)
The lacrimal function has been evaluated in 23 patients suffering from primary biliary cirrhosis by rose bengal test, the Schirmer test 1, and the tear breakup time. Ocular dryness was present in 78% of cases studied. No difference was found with respect to the length or severity of the hepatic involvement between patients with and without lacrimal dysfunction, but in patients with signs of hypolacrimation the changes in the lacrimal tests increased with the duration and histological progression of liver disease.